Tradisi Kaboro Coi di Desa Sakuru Monta, Bima; Analisis Hukum Islam - Hasan, Hamzah (Mazahibuna: Jurnal Perbandingan Mazhab, 2020)
Kaboro Coi practice was originally just a tradition, but the community has considered it an obligation, not carrying out the cooboro coi will get social sanctions from the community, such as being ostracized and the community no longer cares about any event events (hajatan) conducted by families who do not carry out the Kaboro Coi tradition. Seen from the perspective of Islamic law Kaboro coi practice has a substance that shows the value of togetherness, helping each other to help each other, like the concept of "wata ᾶwanu‘ alal birri wa taqwa ". This study, does not want to see the Kaboro Coi tradition as an act that implies rewards and sins when done and not done, but just want to see why this tradition is important to do.The data used as material for analysis are field data obtained through observation, interviews, and literature studies. This paper confirms that the practice of Kaboro Coi, in the terminology of the Sakuru Monta village community, has become a community practice that aims to facilitate the implementation of the celebration, such as sunna ra ndoso labo nika ra neku